Residential Densification for Positive Energy Districts - Bambara, James; Athienitis, Andreas K.; Eicker, Ursula (Frontiers in Sustainable Cities, 2021)
The energy footprint of houses can be reduced by replacing the aging stock with higher density and more energy efficient homes equipped with on-site renewable energy production. In this study, a “double density” simulation scenario is considered where each existing detached house in a community is replaced with two houses of equal living area on the same land lot. The new houses were assumed to be equipped with several energy efficiency measures (envelope, HVAC and domestic hot water) and a building-integrated photovoltaic (BIPV) roof. The TRNSYS software was used to simulate the annual energy performance of the buildings in Montreal, Québec, Canada (45.5°N). It was found that the two new houses, which can accommodate twice the number of people on the same land lot, consumed 35% less energy than the existing house. Individually, each of the new houses required 67% less electricity than the existing house (reduced from 22,560 to 7,350 kWh yr-1). In addition, the BIPV roof installed on the two new houses could generate nearly three times more electricity (43,320 kWh yr-1) than they consumed (14,690 kWh yr-1). Annually, nearly half (47%) of the house’s electricity can be directly supplied by the BIPV system. A significant portion of the annual solar electricity generation (84%), which cannot be directly utilized by the houses, can be stored on-site for later use to increase self-consumption (e.g. power-to-thermal energy or charging electric vehicles) or could be exported to the grid to support decarbonization elsewhere (e.g. production of hydrogen fuel for transportation). The combined effect of energy efficient construction and on-site renewable energy production would enable occupants to shift from consuming 5,640 kWh yr-1 to producing 3,580 kWh yr-1. Residential densification can significantly contribute towards retrofitting existing communities into resilient positive energy districts.